Relationship of water landscapes with the social fabric as a case study: The Peloponnese peninsula - Krasopoulou, Maria; Mitoula, Roido; Theodoropoulou, Helen; Georgitsogianni, Evagelia (Archives of Business Research, 2020)
The object of the research is to highlight the water areas, creating a cultural network in the Peloponnese peninsula. What are the tools to approach a landscape that can help interpret, read, and manage a site? The research methodology was based on geographical features and the selection of sections on the map, linking them to create a cultural network model. Due to the large and rich diversity of water bodies, it was deemed necessary to select five different water landscapes in four different prefectures of the peninsula, looking for different-characteristic forms of water. The Anavalos wetland in Argolida, the river Ladonas in Arcadia, the springs of Lerni in Argolida, the lake Stymfalia and Doxa in Corinth and the Stygos Waters in Achaia were selected as case studies. Through this process, a complete picture emerged in all networking sites. The interviews and personal contacts with the competent social bodies resulted in a comprehensive and more substantial understanding of the issue. Also important was the creation of a questionnaire-experiment, which took place in the Peloponnese, giving very important results-conclusions about the knowledge-views, residents-citizens, the peninsula and the relationship-contact they have with wetlands and their knowledge in relation to mythology. Water has the potential to gain social and political weight, to bring the citizen face to face with the responsibility he has, to manage the environment with respect and consistency, to discover it, if he utilizes it and finally to highlight it as a model of sustainable development.